Comparison of the Effectiveness of Compassion-Focused Therapy and Cognitive-Behavioral Therapy on Experiential Avoidance and Post-Traumatic Growth in Sexually Abused Girls - Rahimian, Afsaneh; Namazi, Mitra; Aghili, Seyed Mojtaba (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: Sexual abuse in its various forms leaves irreversible damages on the physical and psychological development of children and adolescents. This study aimed to compare the effectiveness of Compassion-Focused Therapy (CFT) and Cognitive-Behavioral Therapy (CBT) on experiential avoidance and post-traumatic growth in sexually abused girls.Methods and Materials: The present research was quasi-experimental with a pre-test, post-test design and a control group. The statistical population included sexually abused girls studying in Western Tehran during the 2023-2024 academic year. Forty-five individuals were selected through purposive sampling and randomly assigned to experimental and control groups (each group consisting of 15 individuals). The first experimental group received Gilbert's Compassion-Focused Therapy (2010) and the second experimental group received Hofmann and Otto's Cognitive-Behavioral Therapy (2008) in eight 60-minute sessions. The control group did not receive any psychological treatment. Research instruments included Lisak's Sexual Abuse Questionnaire (2005), Bond's Experiential Avoidance Questionnaire (2011), and Tedeschi and Calhoun's Post-Traumatic Growth Inventory (1996). Data were analyzed using covariance analysis, Bonferroni post hoc test, and SPSS software version 26.Findings: The results showed that Compassion-Focused Therapy was more effective than Cognitive-Behavioral Therapy on experiential avoidance (F=24.91, P=0.001) and post-traumatic growth (F=51.26, P=0.001) in sexually abused girls (p